Performance Characteristics of a Rapid New Immunochromatographic Test for Detection of Antibodies to Human Immunodeficiency Virus - Ribeiro-Rodrigues, Rodrigo (American Society for Microbiology, 2003)
A new immunochromatographic rapid test (Rapid Check HIV 1&2; Núcleo de Doenças Infecciosas) for the detection of antibodies to human immunodeficiency virus type 1 and type 2 in human samples (whole blood, serum, and plasma) was evaluated and compared to the commercially available Determine (Abbott Laboratories). When whole-blood samples were evaluated, the specificity and sensitivity of both tests were 100%. However, when plasma samples were used, sensitivity for the Rapid Check HIV 1&2 and the Determine tests were 100 and 98.58%, respectively. The observed specificity for plasma samples was 98.94% for the Rapid Check HIV 1&2 and 96.97% for the Determine test. The results presented here are encouraging and support the adoption of both tests as an alternative to enzyme-lined immunosorbent assay and/or Western blots in regions where laboratorial infrastructure is not available or for use in the management of occupational accidents for healthcare workers.